Aplicación de auditoría de sistemas a los servicios de integración de datos con procesos ETL (2020)
The auditor should consider as part of his work, the application of knowledge on the characteristics of use, design and automation of ETL processes, which are summarized in extraction, transformation and data loading. Additionally, the risk scenarios established in accordance with the Colombian Technical Standard NTC-ISO 31000, serve as a guide, not only for the ETL designer, but also for the auditor to identify possible risk generating events and therefore the application of controls for their mitigation. Based on the COBIT reference framework, important aspects and criteria are established for the evaluation of ETL processes and their controls. It also presents a list of good practices that a systems auditor should consider when evaluating data integration services.